Affective disorders in the elderly in different European countries: results from the MentDis_ICF65+ study - Andreas, Sylke; Dehoust, Maria; Volkert, Jana; Schulz, Holger; Sehner, Susanne; Suling, Anna; Wegscheider, Karl; Ausín, Berta; Canuto, Alessandra; Crawford, Mike J.; Ronch, Chiara Da; Grassi, Luigi; et al. (PLOS ONE, 2019)
Objectives: Affective disorders are among the most prevalent disorders in the elderly. The present study aims to examine the sociodemographic and clinical correlates of major depressive disorder (MDD) and dysthymia in different European and Associated countries using standardized interview techniques. Furthermore, service utilization for the elderly with depression is assessed. Methods The MentDis_ICF65+ study is a cross-sectional survey (N = 3,142) that was conducted in six different European and Associated countries (Germany, Italy, Spain, Switzerland, England and Israel) with a subsample of n = 463 elderly with any depressive disorder. Results Sociodemographic and clinical correlates, such as gender, age and symptom severity, were significantly associated with MDD and dysthymia in the elderly. Only 50% of elderly with any depressive disorder were treated with psycho- or pharmacotherapy. Conclusion Our findings identified sociodemographic and clinical characteristics for depression risk in the elderly and highlight the need to improve service delivery to older adults who suffer from depression.
Gesehen am 05.10.2020